Effects of Androgen Excess-Related Metabolic Disturbances on Granulosa Cell Function and Follicular Development - Liao, Baoying; Qi, Xinyu; Yun, Chuyu; Qiao, Jie; Pang, Yanli (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disease in women of reproductive age. Ovarian dysfunctions including abnormal steroid hormone synthesis and follicular arrest play a vital role in PCOS pathogenesis. Hyperandrogenemia is one of the important characteristics of PCOS. However, the mechanism of regulation and interaction between hyperandrogenism and ovulation abnormalities are not clear. To investigate androgen-related metabolic state in granulosa cells of PCOS patients, we identified the transcriptome characteristics of PCOS granulosa cells by RNA-seq. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of differentially expressed genes (DEGs) revealed that genes enriched in lipid metabolism pathway, fatty acid biosynthetic process and ovarian steroidogenesis pathway were abnormally expressed in PCOS granulosa cells in comparison with that in control. There are close interactions among these three pathways as identified by analysis of the protein-protein interaction (PPI) network of DEGs. Furthermore, in vitro mouse follicle culture system was established to explore the effect of high androgen and its related metabolic dysfunction on follicular growth and ovulation. Follicles cultured with high androgen exhibited decreased expression levels of cumulus expansion-related genes (Has2, Ptx3, Tnfaip6 and Adamts1) and oocyte maturation-related genes (Gdf9 and Bmp15), which may be caused by impaired steroid hormone synthesis and lipid metabolism, thus inhibited follicular development and ovulation. In summary, our study offers new insights into understanding the role of high androgen induced granulosa cell metabolic disorder in ovarian dysfunction of PCOS patients.